O-012 Combined endovascular embolization and stereotactic radiosurgery in the treatment of large arteriovenous malformations. (16th November 2010) - Blackburn, S; Ashley, W; Rich, K; Simpson, J; Drzymala, R; Ray, W; Moran, C; Cross, D; Chicoine, M; Dacey, R; Derdeyn, C; Zipfel, G
Abstract : Objective: Large cerebral arteriovenous malformations (AVMs) are often not amenable to direct surgical resection or stereotactic radiosurgery (SRS) treatment. An alternative treatment strategy is staged endovascular embolization followed by SRS (Embo/SRS). This study examined the experience at Washington University in St Louis with Embo/SRS for large AVMs, and reviewed results in earlier case series. Methods: 21 patients with large AVMs treated with Embo/SRS between 1994 and 2006 were retrospectively evaluated. AVM size (before and after embolization), procedural complications, radiological outcome and neurological outcome were examined. Radiological success was defined as AVM obliteration by catheter angiography, CT angiography (CTA) or MR angiography (MRA). Radiological failure was defined as residual AVM by catheter angiography, CTA or MRA performed ≥3 years post-SRS. Results: All AVMs in this series were >3 cm in maximal diameter (mean 4.2 cm); 12 (57%) were high grade (Spetzler-Martin 4 or 5). Clinical follow-up was available in 20/21 patients; radiographic follow-up was available in 19/21 patients (mean follow-up time 3.1 years). Of the 43 embolization procedures performed, eight complications occurred, leading to transient neurologic deficits in five patients (24%), minor permanent neurologic deficits in three patients (14%) and no major permanent neurologic deficits (0%). Of the 21 SRS procedures performed, one (5%) radiation induced complication occurred, leading to a permanent minor neurologic deficit. Of the 20 patients with clinical follow-up, none experienced cerebral hemorrhage. Of the 19 patients with radiographic follow-up, AVM obliteration was confirmed by catheter angiography in 12, MRA in two and CTA in two. Residual nidus was found in three patients. In patients with follow-up catheter angiography, AVM obliteration rate was 80% (12/15). Conclusions: Embo/SRS provides an effective means of treating large AVMs not amenable to standard surgical or SRS treatment. The outcomes and complication rates reported in this series compare favorably with other reported therapeutic strategies for this very challenging patient population.